The impact of working on site on individual motivation of software engineers in a South African organisation - Gough, Andrew Carl (My University, 2014)
ABSTRACT South African engineering companies who engage in project execution as part of their core business make use of systems engineers to perform certain project related tasks. Depending on the project phase, it is required that these tasks are completed at the project site, thus requiring the systems engineer to work onsite, away from their homes. Individual motivation of systems engineers is essential to their organisation, and can have a significant effect on project delivery time, productivity, budgets, absenteeism and project success (Beecham, Baddoo, Hall, Robinson, & Sharp, 2008). It is therefore essential for their employing organisations to strive to maintain a high level of motivation among its systems engineers. Working onsite presents both benefits and challenges to the systems engineers, and this may have an effect on the level of individual motivation of these systems engineers. The aim of this study was to assess the impact that working onsite has on the individual motivation of systems engineers in a South African engineering organisation. The research was exploratory and was done using a qualitative technique, making use of semi-structured interviews and thematic analysis. The findings suggest that working onsite has both positive and negative effects on the individual motivation of systems engineers. The findings illustrate the key factors that motivate and de-motivate systems engineers whilst, and due to, working onsite. The key implication of the research is that it is essential that organisations maximise the motivating factors, whilst reducing or mitigating the de-motivating factors that systems engineers perceive to be present whilst working onsite, in order to increase their levels of motivation, or to maintain a high level of motivation.
MBA 2014
Keywords: Employee motivation, Engineering -- Management, Software engineering, Systems engineering